Text-fig. 9. a–e: Carya aff. minor. a: Terminal leaflet, Oriolo MSF 755. b: Oriolo MSF 755. c: Oriolo MSF 766. d: Oriolo MSF 768. e: Oriolo MSF 635. f, g: Pterocarya aff. fraxinifolia. f: Fruit, Oriolo MSF 632. g: Leaflet, Oriolo MSF 632a. h–j: Alnus aff. glutinosa subsp. barbata. h: Oriolo MSF 852. i: Oriolo MSF 850. j: Seed cone, Oriolo MSF 987. k–o: Corylus aff. avellana. k: Leaf, Oriolo MSF 841. l: Fruit, Oriolo MSF 1001. m: Fruit, Oriolo MSF 1022. n: Fruit, Oriolo MSF 1003. o: Fruit, Oriolo MSF 1022. Scale bars 50 mm (a–e, g–i), 10 mm (f, j–o). in The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome - Denk, Thomas; Sami, Marco; Teodoridis, Vasilis; Martinetto, Edoardo (Zenodo, 2022)
Text-fig. 9. a–e: Carya aff. minor. a: Terminal leaflet, Oriolo MSF 755. b: Oriolo MSF 755. c: Oriolo MSF 766. d: Oriolo MSF 768. e: Oriolo MSF 635. f, g: Pterocarya aff. fraxinifolia. f: Fruit, Oriolo MSF 632. g: Leaflet, Oriolo MSF 632a. h–j: Alnus aff. glutinosa subsp. barbata. h: Oriolo MSF 852. i: Oriolo MSF 850. j: Seed cone, Oriolo MSF 987. k–o: Corylus aff. avellana. k: Leaf, Oriolo MSF 841. l: Fruit, Oriolo MSF 1001. m: Fruit, Oriolo MSF 1022. n: Fruit, Oriolo MSF 1003. o: Fruit, Oriolo MSF 1022. Scale bars 50 mm (a–e, g–i), 10 mm (f, j–o). Published as part of Denk, Thomas, Sami, Marco, Teodoridis, Vasilis & Martinetto, Edoardo, 2022, The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome, pp. 217-262 in Fossil Imprint 78 (1) on page 235, DOI:10.37520/fi.2022.009, http://zenodo.org/record/7167867